2018
DOI: 10.1111/ejn.14269
|View full text |Cite
|
Sign up to set email alerts
|

The prodromes of Parkinson's disease

Abstract: Whilst the diagnosis of Parkinson's disease (PD) relies on the motor triad of bradykinesia, rigidity and tremor, the underlying pathological process starts many years before these signs are overt. In this prodromal phase of PD, a diverse range of non‐motor and motor features can occur. Individually they do not allow a diagnosis of PD, but when considered together, they reflect the gradual development of the clinical syndrome. Different subgroups within the prodromal phase may exist and reflect different underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…Most of them often appear earlier than the motor symptomatology, during the so-called prodromal stage and worsen following the disease’s progression ( Schapira et al, 2017 ). Indeed, NMS may manifest several years prior to the onset of motor symptoms, even up to 20 years before the diagnosis, and the prevalence can vary between the patients ( Schapira et al, 2017 ; Rees et al, 2019 ). In this context, although there are not specific NMS for PD, the presence and combination of various NMS as well as the correlation with an early dopamine depletion may be useful for early diagnosis ( Berg et al, 2013 ; Schapira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them often appear earlier than the motor symptomatology, during the so-called prodromal stage and worsen following the disease’s progression ( Schapira et al, 2017 ). Indeed, NMS may manifest several years prior to the onset of motor symptoms, even up to 20 years before the diagnosis, and the prevalence can vary between the patients ( Schapira et al, 2017 ; Rees et al, 2019 ). In this context, although there are not specific NMS for PD, the presence and combination of various NMS as well as the correlation with an early dopamine depletion may be useful for early diagnosis ( Berg et al, 2013 ; Schapira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic REM sleep behavioral disorder (RBD) is an early manifestation of neurodegenerative disorders from the synucleinopathy group; 70–90% RBD patients will eventually develop one of the synucleinopathy phenotypes: Parkinson disease (PD), Lewy body dementia (LBD), or multiple system atrophy (MSA) 1,2 . Therefore, RBD patients along with carriers of mutations causing monogenic PD are best populations to study prodromal synucleinopathy 3 . The term prodromal synucleinopathy refers to the stage wherein early symptoms of neurodegeneration are present, but classic clinical diagnosis based on fully evolved parkinsonism or dementia is not yet possible 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that alpha-synuclein pathology spreads in the nervous system along predisposed pathways and triggers progressive neurodegeneration in susceptible areas 3 . Gradually progressing degeneration of dopaminergic neurons in substantia nigra (SN) in RBD can be visualized as decreasing tracer uptake on repeated dopamine transporter (DAT) imaging 12 .…”
Section: Introductionmentioning
confidence: 99%
“…PD is, therefore, often diagnosed clinically when the synucleinopathy is already advanced. On the other hand, patients frequently report having non-motor symptoms for 10–20 years before the diagnosis ( 3 ). These prodromes, defined as “early (non-specific) symptoms or signs which often indicate the onset of a disease before more diagnostically specific signs and symptoms develop,” provide a potential temporal window during which disease-modifying therapy, once it becomes available, could be administered to prevent or delay the development and progression of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, researchers and clinicians recognize the need for a clinical diagnosis based on quantifiable measures (i.e., biomarkers) to refine qualitative assessments. Characteristic prodromal symptoms of PD are impaired olfaction (anosmia/hyposmia), constipation, depression, excessive daytime sleepiness, rapid eye movement (REM) sleep behavior disorder (RBD), impaired color vision, mild cognitive impairment, and autonomic dysfunction (e.g., orthostatic hypotension (OH), erectile dysfunction, bladder disturbances) ( 1 , 3 ). From a neurochemical point of view, PD was the first neurodegenerative disease of which the underlying neurochemical abnormality was identified, i.e., striatal depletion of the catecholamine dopamine (DA) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%